Representation of Moral Education Values In the Poems of AbÅ« al-â€˜AtÄhiyah (A Study of Genetic Structuralism) - Hermawan, Acep; Fadillah, Roojil; Munib, Munib (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
The poem is one of the literary works that is often used as a medium to convey messages of life. Through rhythmic language and imaginative content it can stimulate feelings and thoughts about the meaning of life. Therefore, it is often used as an educational medium that is believed to effectively influence a person's behavior through moral and ethical messages. Among the collections of poems that contain the message of life are the poems by AbÅ« al-â€˜AtÄhiyah. This research aims to reveal in-depth the values of moral education contained in the 4163 stanzas of AbÅ« al-â€˜AtÄhiyah in the book entitled AbÅ« al-â€˜AtÄhiyah: Asyâ€™Äruhu wa AkhbÄruhu, edited by SyukrÄ« Faishal from the book DÄ«wÄn AbÄ« al-â€˜AtÄhiyah. This research uses a qualitative descriptive method with a genetic structuralism approach. The results showed six themes of life, namely death, worldly life, self-forget, ruler lifestyle, concern for others, and self-introspection. These themes show the formation of a person who has religious behavior, creative and healthy thoughts, honest behavior, hard work attitude in achieving goals, politeness, love of peace, tolerance for others, and responsibility.